HTA Agencies Need Evidence-Informed Deliberative Processes; Comment on "Use of Evidence-Informed Deliberative Processes by Health Technology Assessment Agencies Around the Globe" - Michael Schlander (Kerman University of Medical Sciences, 2021)
There are at least two reasons why health technology assessment (HTA) agencies need to seek process-based solutions to support the legitimacy of healthcare resource allocation, ie, (i) in pluralistic societies, the existence of often conflicting and incommensurable claims (ie, the "fragmentation of value") and the lack of a broadly accepted, ethically defensible analytical framework, and (ii) the well-documented loopholes of the conventional logic of cost-effectiveness (CE) with its reductionist concept of allocative efficiency, which fails to reflect the distributive dimension of resource allocation decisions in collectively financed health schemes.